A short note on the nucleolar size and density in apoptotic leukemic granulocytic precursors (HL-60 cells) - Smetana, Karel; Chan, Pui K; Marinov, Yuri; Soucek, Josef; Hrkal, Zbynek; Busch, Harris (Life sciences, 2004)
The present study was undertaken to provide more information on the nucleolar size and density in mononuclear blastic granulocytic precursors represented by HL-60 cells the proliferation of which was blocked by photodynamic treatment (PDT) which induced apoptotic process without preceding terminal maturation. Both the nucleolar size and density did not change in apoptotic cells in comparison with controls. Thus, large and dense nucleoli in apoptotic cells are not necessarily related to the nucleolar biosynthetic or cell proliferation activity.
Keywords: apoptóza; HL-60 buňky; kyselina aminolevulová; Apoptosis; Silver Staining; Cell Nucleolus; organizátor jadérka; lidé; Photosensitizing Agents; HL-60 Cells; fotosenzibilizující látky; Light; počítačové zpracování obrazu; granulocyty; Nucleolus Organizer Region; Aminolevulinic Acid; barvení stříbrem; Granulocytes; světlo; buněčné jadérko; Image Processing, Computer-Assisted; Humans